True Mangroves of Bintuni Bay, Indonesia with Special Notes on the Existence of Amyema mackayensis (Blakely) Danser and Brownlowia argentata Kurz - Ruhuddien Pandu Yudha; Ary Prihardhyanto Keim; Wawan Sujarwo; Mériadec Sillanpää; Charlie D. Heatubun (Faculty of Forestry Universitas Gadjah Mada, 2024)
This research aimed to identify true mangroves in the ecotone area of Bintuni Bay, West Papua, Indonesia. It applied a plotless transect sampling method to identify two true mangroves previously unknown to the area, namely Amyema mackayensis and Brownlowia Argentata. The presence of the species in Bintuni Bay extended its distribution to the northern area of Indonesian New Guinea. With the addition of these two new records, Bintuni Bay hosted 30 species of true mangroves.